Case Report: Invasive Cryptococcosis in French Guiana: Immune and Genetic Investigation in Six Non-HIV Patients - Goupil de Bouillé, Jeanne; Epelboin, Loïc; Henaff, Fanny; Migaud, Mélanie; Abboud, Philippe; Blanchet, Denis; Aznar, Christine; Djossou, Felix; Lortholary, Olivier; Elenga, Narcisse; Puel, Anne; Lanternier, Fanny; et al. (Frontiers in Immunology, 2022)
Objectives: We describe the clinical, mycological, immunological, and genetic characteristics of six HIV negative patients presenting a cryptococcosis. Methods: Patients with cryptococcosis without any of the classical risk factors, such as HIV infection, followed at Cayenne Hospital, were prospectively included. An immunologic and genetic assessment was performed. Results: Five males and one female were investigated. All presented a neuro-meningeal localization. Cryptococcus neoformans var. gattii and var. grubii, were isolated in two and three patients, respectively, whereas one patient could not be investigated. Overall, we did not observe any global leukocyte defect. Two patients were found with high levels of circulating autoantibodies against GM-CSF, and none had detectable levels of autoantibodies against IFN-γ. Sequencing of STAT1 exons and flanking regions performed for four patients was wild type. Conclusion: To better understand cryptococcosis in patients with cryptococcosis but otherwise healthy, further explorations are needed with repeated immune check-up and strain virulence studies